Islamic State in Iraq and Syria's standardized media and jihadist nation-state building efforts. Issue 3 (September 2019) - Al-Rawi, Ahmed
In its efforts to establish order and legitimacy among the people it once controlled, Islamic State in Iraq and Syria followed standardized and systematic nation-state building policies. The terrorist group attempted to establish an imagined jihadist nation-state with the assistance of standardized media productions and practices. These media productions that are examined in this article reflect Islamic State in Iraq and Syria's unified vision of the ultra-conservative society that it once intended to form in its different territories. I argue here that Islamic State in Iraq and Syria used standardized media productions to promote strict sharia laws including emphasis on men and women's garments, distrust in secular rule, and calls for jihad in the different cities that it controlled. For Islamic State in Iraq and Syria, media is jihad and journalists are Mujahideen whose main purpose is to mobilize the masses and assist in creating a jihadist nation-state.